TRUST Technique for Neurointervention: A Promising Alternative for Complex Cases - Jiang, Xinzhao; Wang, Peng; Liu, Fang; Wu, Huadong; Jiang, Peng; Yuan, Ruozhen; Zhang, Sheng; Shi, Zongjie (Current neurovascular research, 2024)
Neurointervention via Transradial Access (TRA) is becoming increasingly popular as experience with this technique increases. However, approximately 8.6-10.3% of complex TRA cases are converted to femoral access due to a lack of support or radial artery spasm. This study aimed to assess the efficacy and safety of the TRUST (trans-radial coaxial catheter technique using a short sheath, Simmons catheter, and Tethys intermediate catheter) technique in interventional procedures via TRA. This was a single-center retrospective analysis of 16 patients admitted to our institute between January 2023 to May 2023 to undergo endovascular interventions with the TRUST technique via the TRA. The mean age of the study population was 63.8 years, and 62.5% were male (10/16). The most common procedure was intracranial atherosclerotic stenosis (93.75%, 15/16). All procedures were performed successfully, and the most common procedures in our cohort were ballooning (50.0%, 8/16), stenting (18.75%, 3/16), and both procedures combined (31.25%, 1/16). All procedures were performed using the TRA, and the distal and proximal radial arteries were used for access in 31.35% (5/16) and 68.75% (11/16) of the cases, respectively. Technical success was achieved in all patients and most cases demonstrated mTICI ≥2b recanalization (93.75%, 15/16). In this case, no major access-site complications occurred. The TRUST technique is technically safe and feasible and had a high technical success rate and low complication rate in our study. These results demonstrate that the TRUST technique is a promising alternative for patients undergoing complex neurointerventions.